Engineered Exosomes for Tumor-Targeted Drug Delivery: A Focus on Genetic and Chemical Functionalization - Ali Akbari; Fereshteh Nazari-Khanamiri; Mahdi Ahmadi; Maryam Shoaran; Jafar Rezaie (MDPI AG, 2022)
Cancer is the main cause of death worldwide. The limitations in traditional cancer therapies provoked the advance and use of several nanotechnologies for more effective and nontoxic cancer treatment. Along with synthetic nanocarriers, extracellular vesicles (EVs)-mediated drug delivery systems have aroused substantial interest. The term EVs refers to cell-derived nanovesicles, such as exosomes, with phospholipid-bound structures, participating in cell-to-cell communication. Exosomes are 30-150 nm vesicles that can transfer many biological molecules between cells. From a drug delivery standpoint, exosomes can be loaded with various therapeutic cargo, with the several advantages of low immunogenicity, high biocompatibility, transformative, and effective tumor targeting aptitude. The exosomal surface can be functionalized to improve tumor targeting ability of them. Researchers have genetically expressed or chemically linked various molecules on the surface of exosomes. Despite extensive investigation, clinical translation of exosome-based drug delivery remains challenging. In this review, we discuss various methods used to loading exosomes with therapeutic cargo. We describe examples of functionalized exosomes surface using genetic and chemical modification methods. Finally, this review attempts to provide future outlooks for exosome-based targeted drug delivery.